Intensity‐related distribution of sweet and bitter taste fMRI responses in the insular cortex. Issue 12 (8th May 2019) - Canna, Antonietta; Prinster, Anna; Cantone, Elena; Ponticorvo, Sara; Russo, Andrea Gerardo; Di Salle, Francesco; Esposito, Fabrizio
Abstract: The human gustatory cortex analyzes the chemosensory properties of tastants, particularly the quality, intensity, and affective valence, to determine whether a perceived substance should be ingested or rejected. Among previous studies, the spatial distribution of taste intensity‐related activations within the human insula has been scarcely addressed. To spatially characterize a specialized or distributed nature of the cortical responses to taste intensities, a functional magnetic resonance imaging study was performed at 3 T in 44 healthy subjects where sweet and bitter tastants were administered at five increasing concentrations and cortex‐based factorial and parametric analyses were performed. Two clusters in the right middle‐posterior and left middle insula were found specialized for taste intensity processing, exhibiting a highly nonlinear profile across concentrations. Multiple clusters were found activated by sweet and bitter taste stimuli at most concentrations, in the anterior, middle‐posterior, and inferior portion of the bilateral insula. Across these clusters, respectively, for the right and left insula, a superior‐to‐inferior and an anterior‐to‐posterior spatial gradient for high‐to‐low concentrations were observed for the most responsive intensity of both tastes. These findings may gather new insights regarding how the gustatory cortex is spatially organized during the perceptual processing of taste intensity for two basic tastants.